What can Africa Learn from China's Experience in Agricultural Development?. (28th June 2013) - Xiaoyun, Li; Lixia, Tang; Xiuli, Xu; Gubo, Qi; Haimin, Wang
Abstract Recently there has been a growing interest in China's rapid economic growth, particularly concerning the role of agriculture and its impact on poverty reduction. While China and Africa have developed their agricultural sectors under different historical conditions, this article proposes that China's poverty reduction and smallholder‐based agricultural policies can provide a useful model for African countries to develop their own strategies in agrarian change.